090 Using quality improvement methodology to improve fundamental neonatal care at GOSH. (December 2018) - Scott, E; Hannam, S; Kelly, M
Abstract : Context: Following serious incidents around mismanagement of jaundice and missing bloodspot samples, a clinical audit of neonatal care was carried out. This highlighted areas for improvement and a quality improvement project was initiated by the Neonatal Nurse Advisor, Consultant Neonatologist and QI Team. QI methodology and PDSA cycles were used to identify, test and implement change, using measurement to understand variation and monitor the impact of interventions to ensure sustained improvement. Aim: To improve the quality and safety of neonatal care by January 2018, broken down into sub–aims: All cases of neonatal jaundice are managed in line with NICE guidelines. All eligible neonates have a successful bloodspot screening test within the required timescale. All neonates are managed in line with fluid management guidelines. Method: Diagnostic work identifying appropriate improvement approaches (aim setting, driver diagrams, process mapping, and staff survey). A developed real–time report highlighting in–patient neonates to improve oversight of where vulnerable patients situated. Streamlined admission processes to improve the availability of information required for screening. Developed automated email prompt system highlighting babies eligible for screening. Developed a comprehensive programme of neonatal education. Improved access to resources via ward folders and intranet hub. New neonatal care pathway documentation. Awareness raising of fundamental neonatal care. Measures and results: SPC demonstrates sustained improvements for outcome measures: The increase from an average of 62% of neonates managed in line with NICE guidelines to 80%. Decreased from average of 31% of neonates requiring avoidable repeat to 11% Increased from average of 93% of bloodspots within required timeframe to 98%. Challenges and learning: Embedding sustainable change and engagement in light of staff turnover and junior doctor rotation. A clear sustainability plan was developed, outlining responsibilities and accountability for sustaining the quality of practice.